2004
DOI: 10.1074/jbc.m409483200
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-mediated Site-specific DNA Cleavage and Suppression of Promiscuous Activity of KpnI Restriction Endonuclease

Abstract: The characteristic feature of type II restriction endonucleases (REases) is their exquisite sequence specificity and obligate Mg 2؉ requirement for catalysis. Efficient cleavage of DNA only in the presence of Ca 2؉ ions, comparable with that of Mg 2؉ , is previously not described. Most intriguingly, KpnI REase exhibits Ca 2؉ -dependent specific DNA cleavage. Moreover, the enzyme is highly promiscuous in its cleavage pattern on plasmid DNAs in the presence of Mn 2؉ or Mg 2؉ , with the complete suppression of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…However, a comparison of the cofactor preferences of PD-(D/E)XK and HNH REases indicated that HNH enzymes have a greater flexibility for metal ion coordination. For example, R.KpnI, the first REase member of the HNH superfamily to be identified, exhibits broad cofactor utilization for DNA cleavage (10,149,150). This utilization is also seen in nonspecific endonucleases belonging to the superfamily, e.g., colicin E7, colicin E9, and Serratia nuclease (151)(152)(153).…”
Section: Promiscuity In Cofactor Utilization and Substrate Specificitymentioning
confidence: 99%
“…However, a comparison of the cofactor preferences of PD-(D/E)XK and HNH REases indicated that HNH enzymes have a greater flexibility for metal ion coordination. For example, R.KpnI, the first REase member of the HNH superfamily to be identified, exhibits broad cofactor utilization for DNA cleavage (10,149,150). This utilization is also seen in nonspecific endonucleases belonging to the superfamily, e.g., colicin E7, colicin E9, and Serratia nuclease (151)(152)(153).…”
Section: Promiscuity In Cofactor Utilization and Substrate Specificitymentioning
confidence: 99%
“…Modification of the phage genome was carried out by preparing the phage lysates on E. coli BL26 strain overexpressing KpnI MTase (pUCMK). M.KpnI does not exhibit promiscuous behavior and methylates in a site-specific manner (14). The modification status of the phage genomes was confirmed by resistance to site-specific cleavage by KpnI REase both in vitro and in vivo.…”
Section: Methodsmentioning
confidence: 82%
“…The dsDNA breaks catalyzed by REases could be lethal to the host genome if they are not controlled (26). The host cell harboring promiscuous R.KpnI and site-specific M.KpnI (14) needs to protect its genome not only at the canonical sites but at the noncanonical sites. In case of type I R-M systems, it is established that the resident chromosome is recognized as self rather than foreign even in the absence of modification, a phenomenon known as "restriction alleviation" (27,28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations